ABP1–TMK auxin perception for global phosphorylation and auxin canalization - Friml, Jiří; Gallei, Michelle; Gelová, Zuzana; Johnson, Alexander; Mazur, Ewa; Monzer, Aline; Rodriguez, Lesia; Roosjen, Mark; Verstraeten, Inge; Živanović, Branka D.; Zou, Minxia; Fiedler, Lukáš; et al. (Nature (London), 2022)
The phytohormone auxin triggers transcriptional reprogramming through a well-characterized perception machinery in the nucleus. By contrast, mechanisms that underlie fast effects of auxin, such as the regulation of ion fluxes, rapid phosphorylation of proteins or auxin feedback on its transport, remain unclear 1 – 3 . Whether auxin-binding protein 1 (ABP1) is an auxin receptor has been a source of debate for decades 1 , 4 . Here we show that a fraction of Arabidopsis thaliana ABP1 is secreted and binds auxin specifically at an acidic pH that is typical of the apoplast. ABP1 and its plasma-membrane-localized partner, transmembrane kinase 1 (TMK1), are required for the auxin-induced ultrafast global phospho-response and for downstream processes that include the activation of H + -ATPase and accelerated cytoplasmic streaming. abp1 and tmk mutants cannot establish auxin-transporting channels and show defective auxin-induced vasculature formation and regeneration. An ABP1(M2X) variant that lacks the capacity to bind auxin is unable to complement these defects in abp1 mutants. These data indicate that ABP1 is the auxin receptor for TMK1-based cell-surface signalling, which mediates the global phospho-response and auxin canalization. Auxin-binding protein ﻿1 (ABP1) is an auxin receptor that, in complex with transmembrane kinase 1 (TMK1), has a key role in the auxin-induced global phosphorylation of proteins and downstream responses such as vascular regeneration.